Sperm morphology in Estonian and Tori Breed Stallions - Aidnik M; Lundeheim N; Kavak A; Einarsson S (Acta Veterinaria Scandinavica, 2004)
The standard procedure for assessing the breeding potential of a stallion includes the parameter total number of spermatozoa classified as morphologically normal. This study investigated sperm morphology of fresh semen in randomly chosen Estonian (E, n = 8) and Tori (T, n = 7) breed stallions with proven fertility. Two ejaculates were examined from each stallion. An aliquot from each ejaculate was fixed in 1 mL formol-saline immediately after collection and examined with phase-contrast microscope at a magnification 1000× for all types of morphological abnormalities. Furthermore smears were prepared and stained according to Williams (carbolfuchsin-eosin) for a more detailed examination of the sperm heads with light microscope at a magnification 1000×. Analysis of variance was applied to the data, and results are presented as LSmeans (± SE). One T stallion that had a disturbance in the spermatogenesis and one 22-year-old E stallion were not included in the analyses. The T stallions had on average 57.5 ± 4.1% and the E-stallions 74.4 ± 3.8% morphologically normal spermatozoa (p = 0.012). In 4 of 7 T stallions and 7 of 8 E stallions both ejaculates had >50% morphologically normal spermatozoa. There was a significant difference between breeds in mean percentage of proximal droplets (17.3 ± 2.7% and 2.9 ± 2.5% for T and E stallions, respectively; p = 0.003).